HUBUNGAN KUALITAS INTERAKSI PERAWAT TERHADAP KEPUASAN PASIEN - ", Nurhidayati "; Dewi, Wan Nishfa; ", Herlina " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract  Patient satisfaction is one of the indicators in assessing the qualityof hospital services. The effort to improve quality of health care in hospital is to improve the nursing services in nursing care. This study aimed to determine the relationship between patient’ssatisfactionswith quality of nurse’s interaction with patient in PetalaBumiHospital Pekanbaru. Research design of this study was descriptive correlation withcross sectional study. Sample in this study was 105 patients.This study used simple random sampling. Data were collected by using questionnaires consist of two questionnaires to measure interactions of nurses and patient’s satisfaction. Data analisedusedwas univariate and bivariate analize. To measure the correlation between variables che square test was used. The results of this study explained that all of the six aspects of care, ability, attitude, appearance, attention, action, and accountability hadrelationship with patient’s satisfaction was the nurse’sability with ρ value  (0,017) < α (0,05);nurse’s attitude withρvalue 0,006< α (0,05); and nurse’s attention with ρvalue 0,017< α (0,05). It can be concluded that good interaction between nurses and patients can promotepatient’s satisfaction.Nurse’s ability to provide clear information about patient health using great attitude and attention will impact on patients’ satisfaction.Keywords: Nurses-patients interaction, Quality of nursing care, Patient Satisfaction